Paper-based aptasensor for colorimetric detection of osteopontin - Pereira, Ana Cláudia (2022)
This work presents a novel cellulose-based aptasensor for the colorimetric detection of a cancer biomarker, osteopontin (OPN), in point-of-care (PoC) analysis. For this purpose, the cellulose paper was chemically modified with (mercaptopropyl)methyldimetoxisilane to attach the thiolated aptamer, which acts as a biological detection layer. The surface modification was checked by Fourier transform infrared spectroscopy and thermogravimetric analysis. Colorimetric detection was performed using a conventional staining solution, Bradford reagent. The colour analysis was performed by evaluating the RGB coordinates provided by the ImageJ program from the photographs taken with a smartphone. Overall, the biosensor shows good sensitivity with a wide linear range (R=0.998) of 51000ng/mL and a detection limit lower than 5ng/mL in buffer and commercial human serum solution after 30 minutes of incubation. In addition, this aptasensor shows good selectivity to some interfering species such as bovine serum albumin and recombinant OPN. Analytical data obtained from spiked serum samples confirm the accuracy of the method. Importantly, it is a broad-spectrum method that tends to meet the criteria of REASSURED (real-time connectivity, ease of sampling, affordability, specificity, ease of use, speed and robustness, device freedom, and deliverability) for global testing.